1991
DOI: 10.1093/nar/19.24.6699
|View full text |Cite
|
Sign up to set email alerts
|

Upstream box/TATA box order is the major determinant of the direction of transcription

Abstract: Mammalian gene promoters for transcription by RNA polymerase II are typically organized in the following order: upstream sequence motif(s)/TATA box/initiation site. Here we report studies in which the order, orientation and DNA sequences of these three elements are varied to determine how these affect polarity of transcription. We have constructed promoters with an 'octamer' upstream sequence ATTTGCAT (or its complement ATGCAAAT) in combination with several different TATA boxes and initiation (cap) sites, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 51 publications
3
40
0
Order By: Relevance
“…Mammalian core promoters are classi®ed into three groups: (1) TATA boxes, which control the initiation of transcription at about 30 bases downstream (Xu et al, 1992;Hernandez, 1993); (2) GC boxes, which often exist in TATA-less housekeeping genes, control 50 ± 80 bases downstream of initiation, though the initiation sites tend to be scattered (Sehgal et al, 1988;O'Shea-Green®eld and Smale, 1992); and (3) initiator' sequences, which control initiation within its sequence in TATA-less promoters (Smale and Baltimore, 1989;O'Shea-Green®eld and Smale, 1992;Weis and Reinberg, 1992). The human p53 promoter contains neither a TATA nor a GC box, and in this study we demonstrated that PE21 is not a typical initiator sequence since the transcription does not occur within its sequence, but rather initiates at 53 and 55 bases downstream from PE21.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mammalian core promoters are classi®ed into three groups: (1) TATA boxes, which control the initiation of transcription at about 30 bases downstream (Xu et al, 1992;Hernandez, 1993); (2) GC boxes, which often exist in TATA-less housekeeping genes, control 50 ± 80 bases downstream of initiation, though the initiation sites tend to be scattered (Sehgal et al, 1988;O'Shea-Green®eld and Smale, 1992); and (3) initiator' sequences, which control initiation within its sequence in TATA-less promoters (Smale and Baltimore, 1989;O'Shea-Green®eld and Smale, 1992;Weis and Reinberg, 1992). The human p53 promoter contains neither a TATA nor a GC box, and in this study we demonstrated that PE21 is not a typical initiator sequence since the transcription does not occur within its sequence, but rather initiates at 53 and 55 bases downstream from PE21.…”
Section: Discussionmentioning
confidence: 99%
“…PE21 might represent a new class of promoter sequence, or it could be classi®ed into the TATA or GC box group in view of the fact that it directs the initiation of transcription at speci®c downstream points. If the latter is the case, the bidirectional initiation activity of PE21 is not surprising since some TATA and GC boxes, especially the symmetric TATA sequence, often exhibit bi-directional activity (Xu et al, 1992;O'Shea-Green®eld and Smale, 1992). However, in a standard assay, a single TATA or GC box without auxiliary enhancer sequence exhibits almost undetectable promoter activity, whereas that of PE21 alone was signi®cant.…”
Section: Discussionmentioning
confidence: 99%
“…The human p53 promoter does not have a TATA or GC box (35,38). However, the PE21 element within the p53 proximal promoter directs bidirectional initiation activity as found with TATA and GC boxes (35,39,40). The PE21 element functions as a binding site for KLF4, a repressor of p53 transcription that transforms cells as a function of p21 status (24,25,35).…”
Section: Muc1 Repressesmentioning
confidence: 96%
“…However, our refined analysis of MTF-1 binding to different MREs later suggested that MTF-1 is sensitive to methylation of MRE positions 6 and 10, offering a straightforward explanation by the direct mechanism; many MRE sites, notably those of MT-IIA, harbor CpG sites at positions 6 and 10 ( Figure 5A). An additional contribution to inactivation probably comes from CpGs in the initiator region, even though this region in principle is extremely tolerant of many kinds of sequence alterations (Xu et a/., 1991). In fact, transcription from the human MT-IIA initiation region, which harbors several CpG sites, was more strongly inhibited by CpG methylation than that from the 4xMREd-OVEC initiation region, which lacks CpGs and is derived from the -globin gene (Figure 3 righthand panel, arrows 2 and 1, respectively; see also Murray and Grosveld, 1987).…”
Section: Transcription From 4xmred and Natural Metallothionein Promotersmentioning
confidence: 99%